AN ANALYSIS OF OBSCUUR LIBEL AS A MANIFESTATION OF THE TENSION BETWEEN CIVIL PROCEDURAL FORMALISM AND ACCESS TO JUSTICE - Pri Pambudi Teguh (EKSEKUSI, 2026)
The application of obscuur libel in civil procedural law practice is frequently used as a basis for declaring claims inadmissible without examining the merits of the case. This condition raises legal concerns because civil procedural law is intended to function as a mechanism for the protection of rights and access to justice within the framework of the rule of law. This study aims to analyze the normative construction of obscuur libel in Indonesian civil procedural law from the perspective of procedural formalism and the principle of the rule of law, as well as to examine the implications of its formalistic application for access to justice and legal protection for justice seekers. This research employs normative legal research using statutory and conceptual approaches, analyzed through a descriptive-qualitative method. The findings indicate that obscuur libel has developed as a doctrinal concept shaped by judicial practice and remains strongly influenced by procedural formalism. Furthermore, the disproportionate application of obscuur libel undermines access to justice, procedural fairness, and legal protection for justice seekers in civil proceedings. Keywords: obscuur libel, civil procedural law, rule of law.